Support Emergence of Home-Grown Policies by Putting Local Partners in the Drafting Seat - Norman, Martin (World Bank, Washington, DC, 2012)
In September 2007, the Government of Bangladesh (GoB) requested that the Board of Investment draft an economic zones policy (EZ Policy). The policy was to cover the entire zone regime of Bangladesh, including export processing zones, industrial estates, and special economic zones, both public and private. Export processing zones had long been a key tool in Bangladesh for creating jobs and increasing exports. In addition, there were 67 industrial estates - at least one in each of Bangladesh's 64 districts - which catered primarily to the domestic market. Both the eight export processing zones and the industrial estates had mixed success. When the GoB commissioned the EZ Policy, the IFC Bangladesh Investment Climate Fund (BICF) agreed to fund the drafting of the policy. In doing this, IFC BICF could have contracted an international consulting company with world-wide expertise in drafting EZ Policies in multiple countries to draft the ideal policy that would have incorporated the best international practices available, avoided common pitfalls in developing economic zones, and relied on the traditional wisdom of the best practitioners.